Antithrombotic activity of Mentha longifolia in animal model - Alamgeer, .; Ain, Qurat ul; Hasan, Umme Habiba; Asif, Hira (Bangladesh Journal of Pharmacology, 2018)
The present research work was conducted to appraise the antithrombotic activity of Mentha longifolia using in vitro and in vivo experiments. Aqueous methanolic (70:30) extract produced significant (p<0.01-0.001) and dose-dependent increase in in vitro blood clotting time, bleeding time, prothrombin time and activated partial thromboplastin level with maximum effect at highest concentration. While in in vivo experiment, aqueous methanol extract showed noteworthy (p<0.01-0.001) prolongation in bleeding time and clotting time after 30, 60 and 90 min of administration except for 25 mg/kg at 30 min which is non-significant. Moreover, plant extract exhibited considerable increase (p<0.1-0.001) in bleeding time, clotting time, prothrombin time as well as activated partial thromboplastin time in rabbits after seven days of treatment. Additionally, HPLC analysis of M. longifolia aqueous methanolic extract illustrated the presence of various valuable phytoconstituents. In a nutshell, M. longifolia possesses potential antithrombotic activity and hence systematically proved to be beneficial in patients with vascular diseases.